Qur'anic solution to women's problems in workplace of Bangladesh - Hossen, Belayet
This research deals with some of the major issues involving working women in Bangladesh, especially in the garment industry which is the second highest foreign currency earner for the Bangladeshi economy. Throughout the country, there are more than six thousand garment and textile industries where about six million labourers are employed and majority of them are women. Such a big number of working women has given rise to challenging issues and situations which can potentially have a deep social and religious impact on the country's economy. This research explains these challenges by using the deductive and analytical methods. The number of working women will gradually decline; consequently, the economic growth of Bangladesh will be greatly affected. The explored problems include salary discrimination between male and female workers, late salary payment to workers, sexual, verbal and harassment, inadequate leave during sickness and pregnancy, inadequate medical facilities, housing problem, insufficient transportation, emergence of various types of diseases and unhygienic workplace due to industrial discharges. The research has identified these problems through an intensive study of previously and currently published research books, papers, magazine articles, governmental and different NGOs' periodicals, surveys and newspapers. The research endeavoured to examine and solve these problems through the Qur'ānic and Prophetic traditions. This research concluded with some crucial findings: Establishing justice in salary of workers, providing training on Islamic rituals and traditions, providing adequate medical facilities, and providing leisure and personal time, dress code for women in accordance to the Islamic and Bangladeshi customs, establishing prayer halls, prohibition of verbal and sexual and other forms of harassment and prevention of adultery.